Pengembangan Animasi Virtual Karakter Anak dengan Autisme dengan Model ADDIE - Rahadian Kurniawan; Febriana Kurniasari; Restu Rakhmawati (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
The increase in the number of people with autism in Indonesia is followed by an increase in the need of teachers. The main problem related to teaching children with autism is the lack of teaching skills in dealing with children with autism. One of the methods used by prospective teachers of children with autism to improve their teaching skills is by playing role-changing dramas. One person plays the role of a teacher, while the other plays a child with autism. From interviews conducted with several autistic special education students, this method was considered less effective in understanding and responding to children with autism. Nowadays, Virtual Reality (VR) allows prospective teachers to practice improving their teaching skills in a safer environment. Generally, the learning simulation process using VR utilizes virtual humans who have specific features and abilities. This study presents the ADDIE model's use to develop virtual human animation used as a learning agent for prospective teachers of children with autism. The animation represents movements which are often performed by children with autism that can be used as a VR module. From the test results, it is known that the animation developed is considered to represent the behavior of children with autism.